Effect of factors on the red pigment production in the stirred drum bioreactor: fractional factorial design approach - Farhan, Mohd Said; Mohamad Al Aamin, Razali (AIP Publishing LLC., 2019)
Public demands on natural colouring over the synthetic colouring are growing due to consumer health concern towards the effect of synthetic colouring. The colorants production by employing fermentation process shows certain advantages. This research has emphasized on the capability of stirred drum bioreactor on performing red pigment in solid-state fermentation (SSF) of Monascus purpureus FTC 5357 by using oil palm frond (OPF). A Fractional factorial experimental design 24 (FFD) was applied in order to evaluate the effect of initial moisture content (IMC), inoculum size, percentage of peptone, pH, aeration rate, loading capacity and agitation programme on the red pigment production. In the FFD experimental studies, the highest pigment production was obtained at 75% (v/w) initial moisture content, 10^8 spores/mL of inoculum size, initial pH of 4, aeration rate of 1.21 vvm, loading capacity of 35% (v/v), agitation programme of 6 cycles/day, with the yield of 71.86 AU/g. The initial moisture content had the most pronounced affects to the red pigment production, followed by the aeration rate of stirred drum bioreactor, peptone concentration and inoculum size. The loading capacity of the bioreactor, agitation programme and the initial pH had the lesser effect to the red pigment production. The result indicated that FFD was a useful tool to improve the red pigment production in SSF using stirred drum bioreactor by considering all the factors involved.